Flexibility Analysis Of Inventory Cost Model With Ergonomics - Korkulu, Sezen; Bona, Krisztina (International Journal of Engineering and Management Sciences, 2019)
The economic and environmental sustainability issues in supply chain management have integrated by many researchers in the past decades. The ergonomics as a social aspect of sustainability had received a little attention by researchers. Therefore, the aim of the paper is analyzing the flexibility of developed inventory cost model with relaxation allowance and endurance time as a social aspect of sustainability. The effects of distance, unit weight of item and total number of items on relaxation allowance, the total cost of logistics operation and the EOQ model were investigated. The analyzed mathematical model was a single operator-single material model which covered transportation of fixed amount of raw materials from storage plant to production plant by manual material handling with simple cart and picking, storing, pushing and pushing back with empty cart for manual handling of the products. The different parameter values applied for analysis such as total amount of handled items (Q) changes between 500 pcs to 2750 pcs, unit weight of item (w) changes between 0.1 kg to 1 kg, distance of movement by manual material handling for picking and storing motions (d1) changes between 2 m to 3 m and the distance between the storing equipment and the supermarket of the production line for pushing motion (d2) changes between 15 m to 20 m. The results of the analysis indicated that the longer the distance of movement for all motions leads to decrease in savings of the model compared to EOQ model. The increase in unit weight of item is increase the savings obtained from application of our model and decrease the optimal lot size. There was no specific change on savings or optimal lot size as the total amount of handled item is increase. The compared results indicated that an increase in d1 and d2 lead to an increase in optimal lot size and increase in total cost of the model. Consequently, the analysis has shown that a decrease in lot size would be the better way to improve both ergonomic conditions and total cost of production in any different parameter values. Finally, the analysis of the inventory model with ergonomics were proved that this model is suitable for different industrial practices.